Pemanfaatan sumber daya alam masa prasejarah berdasarkan temuan arkeologis Gua Arca, Pulau Kangean, Jawa Timur - nfn. Alifah; Harry Widianto; Mohammad Dziyaul Fikriy Arrozain; Rizka Purnamasari; Yuni Suniarti; Mirza Ansyori (Balai Arkeologi Yogyakarta, 2022)
This paper discusses the exploration and utilization of natural resources by a cave-dwelling community. Data was obtained from the excavation at Gua Arca site in Kangean Island, Sumenep, East Java. The results from ecofact analysis and micro-botanical residue analysis on artifacts show the adaptation pattern of the inhabitants of this island by optimizing the exploration of terrestrial and marine resources. During the early occupancy period of c. 6000 BP, there was a fairly dominant use of terrestrial resources, indicated by open forest animal remains, such as Cervidae, Bovidae, Macaca sp., as well as small animals, such as Cercopithecidae, Rodentia, and Varanidae. In the later period of c. 900 BP, the exploitation of natural resources shifted to marine resources, which mainly from the mangrove forest and intertidal zones. Plant utilization was indicated by the presence of wild bananas, wild rice, coconuts, tubers, and the intensive use of Zingiberaceae plants.